2009
DOI: 10.3758/mc.37.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and inhibitory control across the life span: Intrusion errors in the Reading Span Test

Abstract: The aim of this study was to examine to what extent inhibitory control and working memory capacity are related across the life span. Intrusion errors committed by children and younger and older adults were investigated in two versions of the Reading Span Test. In Experiment 1, a mixed Reading Span Test with items of various list lengths was administered. Older adults and children recalled fewer correct words and produced more intrusions than did young adults. Also, age-related differences were found in the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 46 publications
2
51
0
5
Order By: Relevance
“…The analysis of intrusion errors in this task, computed as the number of nonfinal words that the subjects recall, provides a direct and objective measurement of interference control abilities. Using this task, some researchers have found significantly more intrusion errors in older than in young adults (Robert, Borella, Fagot, Lecerf, & Ribaupierre, 2009), while other researchers have not (Schelstraete & Hupet, 2002). However, variations in the reading span test have demonstrated that an interference control failure might account for poor performance on this task, but so also might proactive interference from previous trials (Lustig, May, & Hasher, 2001;May, Hasher, & Kane, 1999), the length of the reading span task (Robert et al, 2009), or the subjects' reading skills (Chiappe, Hasher, & Siegel, 2000;De Beni, Palladino, Pazzaglia, & Cornoldi, 1998).…”
mentioning
confidence: 97%
“…The analysis of intrusion errors in this task, computed as the number of nonfinal words that the subjects recall, provides a direct and objective measurement of interference control abilities. Using this task, some researchers have found significantly more intrusion errors in older than in young adults (Robert, Borella, Fagot, Lecerf, & Ribaupierre, 2009), while other researchers have not (Schelstraete & Hupet, 2002). However, variations in the reading span test have demonstrated that an interference control failure might account for poor performance on this task, but so also might proactive interference from previous trials (Lustig, May, & Hasher, 2001;May, Hasher, & Kane, 1999), the length of the reading span task (Robert et al, 2009), or the subjects' reading skills (Chiappe, Hasher, & Siegel, 2000;De Beni, Palladino, Pazzaglia, & Cornoldi, 1998).…”
mentioning
confidence: 97%
“…Two tasks were used for WM assessment: one verbal (the reading span test, RSpan; de Ribaupierre & Bailleux, 1995;de Ribaupierre, Ghisletta, & Lecerf, 2006;Robert, Borella, Fagot, Lecerf, & de Ribaupierre, 2009, adapted from Daneman & Carpenter, 1980 and one visuospatial (the matrices task; de Ribaupierre et al, 2006;Lecerf & de Ribaupierre, 2005). Each task contained two phases: (a)span assessment and (b)administration of ten trials at span level and administration of ten trials at span+1 level.…”
Section: Working Memory Assessmentmentioning
confidence: 99%
“…Therefore, the span tasks may not be conceived as pure working memory tasks but as double tasks that challenge our ability to successfully divide our attention. Indeed, for this reason, this task has been extensively used to investigate interference control mechanisms, such as inhibition (e.g., Robert et al 2009). …”
Section: Introductionmentioning
confidence: 99%